RANCANG BANGUN SISTEM INFORMASI ADMINISTRASI KOPERASI - Suci Laela Ramdhani (PROCEEDING STIMA)
Cooperatives are associations of people who join and conduct joint ventures on the basis of cooperative principles. So, getting greater benefits at lower costs through companies that are owned or supervised democratically by their members. Information technology is currently one of the needs that cannot be ignored for various activities in cooperatives. The role of computer usage is also expected to be a tool in every activity pengkoperasian where information needs can be more quickly and accurately, so that decision making in everything can be taken in a short time. Cooperative Employee Republic of Indonesia (KPRI) Kokardan Majalengka regency is one form of cooperative that runs its business to provide services to members of the Business Unit Savings and Loans and Business Unit Waserda. With the creation of a data processing information system in the cooperative, it is expected to improve the efficiency and effectiveness of cooperative work.